Determinants of e-participation in the citizens and the government initiatives: Insights from India. (September 2016) - Alathur, Sreejith; Vigneswara Ilavarasan, P.; Gupta, M.P.
Abstract: The paper attempts to examine the determinants of two types of citizens' e-participation – initiated by the citizens and the government. The factors of e-participation were delineated from a review of democracy and e-participation literature and a regression model was developed. On the basis of 407 responses collected through an online and offline survey among the Indian participants, the model was tested. The analysis showed that the citizens' participation efficacy and values determine e-participation of both types. For the citizens' initiatives freedom to participate and legal support for the participation efforts were also the determining factors. The extant research on types of e-participation services is inadequate. The paper attempted to fill the gap and contributes in i) explaining the importance of facilitating multiple stakeholders' initiatives for improved citizens' participation ii) differentiating determining factors among e-participation initiatives and iii) suggesting policy recommendations for successful e-participation initiatives. The future research can focus on determinants for collaborative service initiatives from the citizens and government. Highlights: Examine the determinants of two types of citizens' e-participation – initiated by the citizens and the government. 407 responses collected through an online and offline survey among the Indian participants, the model was tested. citizens' participation efficacy and values determine e-participation of both types. Earlier research on types of e-participation services is inadequate. The paper attempted to fill the gap. paper contributes i) explaining the importance of facilitating multiple stakeholders' initiatives ii) differentiating determining factors iii) policy recommendations for e-participation initiatives.